Why Did Čiurlionis Write the Word Decadence in Quotes? The Analysis of His February 1902 Letter to His Brother Povilas - Okulicz-Kozaryn, Radosław (Colloquia, 2021)
The paper offers a philological and contextual analysis of the word decadence as it was employed in Mikalojus Konstantinas Čiurlionis’s letter to his brother Povilas dated 6 February 1902. The Lithuanian artist implored his relative not to delve into his inner self because of the risk of falling into depression. Using his brother’s confessions, his own introspection, and intellectual experience, Čiurlionis explores this issue quite extensively. In his approach he refers to the theory of nervousness, uses the concepts of self-analysis and decadence, putting the latter in quotes. The quotes mark sender’s intention to dissociate himself from the phenomenon, as well as his confusion about its ambiguous meaning. In fact, as a result of the 19th-century scientific scepticism, the word decadence discredits every attempt at defining it. A careful study of term’s history and career at the turn of 19th century shows that Čiurlionis’s position mirrors uncertainty surrounding the notion in the Western countries, since it has been associated with the contemporary culture by Charles Baudelaire and Pierre Bourget. Some major controversies over the meaning of the word are recounted in the paper. Authors in Paris and London and especially the Warsaw artistic society, which gathered around Zenon PrzesmyckiMiriam and his art magazine “Chimera,” are presented as important in understanding Čiurlionis’s views.
Keywords: Mikalojus Konstantinas Čiurlionis; decadence; nervousness; symbolism; magazine Chimera; Zenon Przesmycki-Miriam